Development and Validation of a Mechanistic, Weather-Based Model for Walnut Blight Caused by Xanthomonas arboricola pv. juglandis - Ji, Tao (Plant disease, 2024)
Walnut blight, caused by Xanthomonas arboricola pv. juglandis (Xaj), occurs worldwide in almost all areas where the Persian walnut (Juglans regia) is grown, causing significant reductions in nut yield via defoliation and fruit drop. The disease control relies on the calendar-based, repeated use of chemical bactericides, negatively impacting economic and environmental sustainability and potentially inducing Xaj resistance to chemicals. This study developed and validated a mechanistic model incorporating the main stages of the pathogen's life cycle and the influence of weather under orchard conditions to improve the scheduling of disease control interventions. The model can simulate: i) the mobilization of primary inoculum; ii) the infection caused by bacteria; and iii) the lesion formation and production of secondary inoculum. We evaluated the model against 21 independent walnut blight epidemics in Italy (nine epidemics on leaves in five orchards) and the USA (12 epidemics on fruit in six orchards). Overall, the model provided accurate predictions for both the occurrence and non-occurrence of infection, with a precision and F1-score of 0.866 and 0.844, respectively. The model could accurately predict disease progression across the season, with a concordance correlation coefficient between observed and predicted disease severities of 0.951, a root mean square error of 0.069, and a coefficient of residual mass of 0.024. After further validation, the model can serve as a decision-making tool for the risk-based timing of chemical sprays in walnut blight management